2015
DOI: 10.1089/apc.2015.0091
|View full text |Cite
|
Sign up to set email alerts
|

Neuroretinal Degeneration in HIV Patients Without Opportunistic Ocular Infections in the cART Era

Abstract: Subtle structural and functional retinal abnormalities, termed 'HIV-associated Neuroretinal Disorder (HIV-NRD)', have been reported in HIV patients receiving combination antiretroviral therapy (cART), without infectious retinitis or any apparent fundus abnormalities otherwise. In this review, we provide an overview of studies investigating HIV-NRD in HIV patients without opportunistic ocular infections in the cART era, and try to elucidate underlying mechanisms and associated risk factors. Most studies focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 89 publications
1
10
0
1
Order By: Relevance
“…Since the large majority of children was cART treated, we cannot differentiate between effects of HIV and different antiretroviral drugs, each of which may have specific contributions to immune activation, vascular dysfunction, and neurotoxicity in chronic HIV-infection. 5,6 Due to the crosssectional design, we are unable to draw conclusions about cause and effect of the observed associations. Ideally, pathogenesis of retinal changes is investigated by detailing the histopathology of retinal changes and evaluating the presence of biomarkers in the vitreous humor of the eye.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the large majority of children was cART treated, we cannot differentiate between effects of HIV and different antiretroviral drugs, each of which may have specific contributions to immune activation, vascular dysfunction, and neurotoxicity in chronic HIV-infection. 5,6 Due to the crosssectional design, we are unable to draw conclusions about cause and effect of the observed associations. Ideally, pathogenesis of retinal changes is investigated by detailing the histopathology of retinal changes and evaluating the presence of biomarkers in the vitreous humor of the eye.…”
Section: Discussionmentioning
confidence: 94%
“…4 The pathogenesis of retinal and cerebral abnormalities in pediatric HIV is poorly understood, and may not only involve direct injury by HIV and/or antiretroviral therapy (cART), but also chronic immune activation, inflammation, and microvasculopathy. 5,6 Several biomarkers associated with systemic inflammation are increased in plasma of HIV-infected children, including C-reactive protein (CRP), monocyte chemoattractant protein (MCP-1), soluble CD14 (sCD14), soluble intercellular cell adhesion molecule-1 (sICAM-1), and soluble vascular cell adhesion molecule-1 (sVCAM-1). [7][8][9][10][11] Studies in HIV-infected adults report that immune activation and inflammation correlate with biochemical and neuroimaging markers of neuronal injury, including elevated cerebrospinal fluid (CSF) levels of neurofilament light chain (NFL), poorer white matter microstructural integrity, and altered magnetic resonance spectroscopy neurometabolites.…”
mentioning
confidence: 99%
“…18 HIV-NRD is part of a spectrum of abnormalities in HIV patients considered by some to potentially represent accelerated biological aging associated with HIV infection. 19,20 The disorder (defined by many studies as having a Pelli Robson contrast sensitivity < 1.5 logCS 21 ) is more common among HIV patients with (prior) severe immune-deficiency, with a prevalence reportedly between 3% and 16% and an estimated cumulative incidence at 20 years after AIDS diagnosis as high as 51%. 22 A recent study found that AIDS patients with HIV-NRD have considerably increased risks of bilateral visual impairment and even blindness in the long term versus those without HIV-NRD.…”
mentioning
confidence: 99%
“…Significant overall pRNFL thinning was found in other studies, but affected only PLHIVs with CD4+ T-cell count nadirs <100 cells/μL for �6 months, compared to PLHIVs with nadirs >100 cells/μL [21,22] or HUCs [21,23]. However, many HIV variables were missing in those reports: (1) HIV-seropositivity duration [22,23,[42][43][44], (2) cART duration [22][23][24]44,45], (3) current plVL or duration of undetectability [21][22][23][42][43]46] and (4) current CD4+ T-cell counts [22,23,43,45]. Hence, those studies' results cannot explain whether the pRNFL thinning could be attributed to severe immunodeficiency alone or its combination with prolonged HIV infection without sustained immunovirological control.…”
Section: Plos Onementioning
confidence: 80%